2004
DOI: 10.1038/sj.sc.3101601
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of morbidity and rehospitalisation following spinal cord injury

Abstract: Study design: Longitudinal, descriptive design. Objectives: The aim of this study was to investigate the frequency, cause and duration of rehospitalisations in individuals with spinal cord injury (SCI) living in the community. Setting: Australian spinal cord injury unit in collaboration with State Health Department. Methods: A data set was created by linking records from the NSW Department of Health Inpatient Statistics Collection between 1989-1990 and 1999-2000 with data from the Royal North Shore Hospital (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
4
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(123 citation statements)
references
References 14 publications
4
107
4
8
Order By: Relevance
“…1,5 In the Australian study, Middleton et al, using data with the Royal North Shore Hospital SCI Database in New South Wales from 1989-1990 to 1999-2000 in 432 patients, reported an overall rehospitalization rate in the first 12 months after discharge of 36%. In the Canadian study, the cases were from 1992 and 1994 and, in the first year following discharge, 22.5% were rehospitalized, which is similar to the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5 In the Australian study, Middleton et al, using data with the Royal North Shore Hospital SCI Database in New South Wales from 1989-1990 to 1999-2000 in 432 patients, reported an overall rehospitalization rate in the first 12 months after discharge of 36%. In the Canadian study, the cases were from 1992 and 1994 and, in the first year following discharge, 22.5% were rehospitalized, which is similar to the current study.…”
Section: Discussionmentioning
confidence: 99%
“…5 These studies have reported that approximately one-third of persons with a traumatic SCI will be rehospitalized each year. 6 These hospitalizations are not only costly to the healthcare system but also to the individual with SCI in terms of increased difficulty in obtaining or sustaining employment or becoming involved in other gainful or leisure activities and a reduced quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…4 Mean LOSs ranging from 4 to 34 days are reported. 1,[3][4][5]10,13,31 In a comprehensive Australian review of hospital readmissions, 58.6% had been readmitted to hospital for an SCI-related episode on one or more occasions over 10 years with an average LOS of 15.5 days. 31 The reasons for hospitalization are similar in all studies, with respiratory, skin and urinary complications contributing to the majority of admissions.…”
Section: Hospitalizationmentioning
confidence: 99%
“…The researcher developed this instrument based on a previous study (Middleton et al, 2004). The final data gathering sheet was divided into sections A and B.…”
Section: Instrumentationmentioning
confidence: 99%
“…These may interfere with health and well being, social activity, produtive employment and quality of life (Middleton et al 2004;Ackery et al 2004). Patients are often re admitted to hospital due to complications with the genitourinary, gastrointestinal, skin, musculoskeletal, neurological, respiratory and cardiovascular systems (Middleton et al 2004;Savic et al 2000). The occurrence of pressure sores is among the most common long term secondary medical complication in persons with SCI (Garber and Rintala 2003).…”
mentioning
confidence: 99%